Problem-Solving Skills’ Analysis Of High School Students In Medan On Reproductive System Material - Badres, Shofi Azzhara; Adlini, Miza Nina (BIOEDUKASI, 2024)
Education in the 21st century aims to build the ability of students' intelligence in learning to solve problems in everyday life. This study aims to determine students' problem-solving ability in the field of reproductive system and investigate the factors that influence it. This study used quantitative research with descriptive method and involved 29 students. Data was collected through distributing questionnaires with 32 statements and 10 essay questions on problem solving ability to determine the truth of descriptive statistics and analyze the factors that influence students' problem solving ability and their data. Data analysis shows the average presentation of the questionnaire problem solving ability of MAS Muhammadiyah 1 Medan of 63% is included in the sufficient category. While the test results of the problem solving ability analysis questions on the material of the human reproductive system, MAS Muhammadiyah 1 Medan obtained an average of 43% including in the very weak category. students' problem solving ability is fairly weak due to several factors that influence it, namely the lack of student learning motivation, the ability to solve problems that are empowered has not been maximized.